The interaction of feeding an eubiotic blend of essential oils plus 25-hydroxy-vit-D3 on performance, carcass characteristics, and dietary energetics of calf-fed Holstein steers - Latack, Brooke C.; Carvalho, Pedro H. V.; Zinn, Richard A. (Frontiers in Veterinary Science, 2022)
Bans on the use of ionophores in several regions of the world has led to a need to identify alternative feed additivies to be added in cattle diets. Essential oil blends have been identified as a potential alternative to ionophores in feedlot diets. The objective of this study was to evaluate the effects of a supplemental a blend of essential oils and 25-hydroxyvitamin D3 on growth performance, energetic efficiency, and carcass characteristics in calf-fed Holstein steers. Ninety Holstein steer calves (123 ± 7 kg; 4 months old) were randomly assigned to 18 pens (5 steers/pen; 6 pens/treatment). Dietary treatments consisted of a steam-flaked corn-based diet supplemented with (DM basis): (1) no additives (CON); (2) 30 mg/kg DM of monensin (MON); (3) 200 mg/kg DM of a mixture of essential oils plus 25-hydroxyvitamin D3 (EO+HYD). There were no treatment effects (P > 0.05) on initial, intermediate and final cattle live weight; moreover, cattle had similar (P > 0.05) average daily gain (ADG) and dry matter intake (DMI) among dietary treatments. However, during the first 112 days of feed, calf-fed Holstein steers supplemented with EO+HYD had a greater (P ≤ 0.05) gain to feed ratio (G/F) than cattle fed the control diet but similar (P > 0.05) G/F to cattle supplemented with MON. However, there was no effect (P > 0.05) of dietary treatments on 112 to 286 d and the overall G/F ratio of calf-fed Holstein steers. Calf-fed Holstein steers supplemented with EO+HYD had greater (P ≤ 0.05) estimated net energy for maintenance (NEm) and net energy for gain (NEg) based on cattle growth performance than cattle fed the CON diet. Cattle supplemented with MON had an intermediate and similar (P > 0.05) NEm and NEg compared to the other two dietary treatments. However, when observed vs. expected NEm and NEg were calculated, cattle supplemented with MON and EO+HYD had greater efficiency of dietary energy utilization than cattle fed the CON diet. Calf-fed Holstein steers supplemented with MON had greater (P < 0.05) fat thickness than EO+HYD supplemented steers, and both were intermediate (P ≥ 0.05) to that of cattle fed the CON diet. There were no other effects (P > 0.05) on kidney, pelvic and heart fat, longissimus area, marbling score, and retail yield. The health status of cattle and liver abscesses or liver scars at slaughter were similar (P > 0.05). We conclude that supplementing calf-fed Holstein steers with MON or EO+HYD for over 285 days increased dietary net energy utilization for maintenance and gain of the diet by 3 and 4%, respectively, compared to non-supplemented steers.